Internal Evaluation of the Endodontics Department School of Dentistry Tehran University of Medical Sciences - Mohamad Zarrabian; Fereshte Farzianpour; Hasan Razmi; Mohamadreza Sharifian; Sedighe Khedmat; Mohamadsaied Sheykh-rezaee; Kazem Ashofteh; Vahiad Alavie (Kerman University of Medical Sciences, 2009)
Background & Objective : Internal evaluation is a process concerning information collection and judgment in order to improve educational activities Considering some facts related to educational measurement and collecting information will lead to a better understanding of the mentioned process In this study we conducted the internal evaluation of the endodontics department in Tehran University of Medical Sciences which is responsible for training dentistry students and residents Methods : In this descriptive study internal evaluation was conducted using 10 steps in 9 fields including management and organization faculty members learners human resources and support educational research and other atmospheres facilities regarding education research etc courses educational programs teaching and learning process patients and finally graduates satisfaction Data was collected using observation interview questionnaire and checklist Results : According to the definition of satisfactory results of this study were mostly qualitative and in some cases they were quantitative The average result of the internal evaluation of the endodontics department in the school of dentistry considering 9 fields was 737% which was considered as approximately satisfactory The results for fields like faculty members and learners were satisfactory (100% and 778% respectively) Atmospheres and educational facilities were unsatisfactory (both were 46%) Conclusion : According to the results atmospheres and educational facilities which were identified as the weakest fields need more consideration and investigation